Nuclear Factor [kappa]-B Is Activated in the Pulmonary Vessels of Patients with End-Stage Idiopathic Pulmonary Arterial Hypertension - Price, Laura C; Caramori, Gaetano; Perros, Frederic; Meng, Chao; Gambaryan, Natalia; Dorfmuller, Peter; Montani, David; Casolari, Paolo; Zhu, Jie; Dimopoulos, Konstantinos; Shao, Dongmin; Girerd, Barbara; et al. (PloS one, 2013)
To assess activation of the inflammatory transcription factor NF-kappa B (NF-[kappa]B) in human idiopathic pulmonary arterial hypertension (PAH). Idiopathic PAH is a severe progressive disease characterized by pulmonary vascular remodeling and excessive proliferation of vascular cells. Increasing evidence indicates that inflammation is important in disease pathophysiology. NF-[kappa]B-p65 and CD68, CD20 and CD45 were measured by immunohistochemistry and confocal microscopy on lung specimens from patients with idiopathic PAH (n = 12) and controls undergoing lung surgery (n = 14). Clinical data were recorded for all patients including invasive pulmonary hemodynamics for the PAH patients. Immunohistochemical images were analyzed by blinded observers to include standard pulmonary vascular morphometry; absolute macrophage counts/mm.sup.2 and p65-positivity (p65+) using composite images and image-analysis software; and cytoplasmic:nuclear p65+ of individual pulmonary arterial endothelial and smooth muscle cells (PASMC) in 10-20 pulmonary arteries or arterioles per subject. The expression of ET-1 and CCL5 (RANTES) in whole lung was determined by RT-qPCR. Macrophage numbers were increased in idiopathic PAH versus controls (49.0±4.5 vs. 7.95±1.9 macrophages/100 mm.sup.2, p<0.0001): these macrophages demonstrated more nuclear p65+ than in macrophages from controls (16.9±2.49 vs. 3.5±1.25%, p<0.001). An increase in p65+ was also seen in perivascular lymphocytes in patients with PAH. Furthermore, NF-[kappa]B activation was increased in pulmonary arterial endothelial cells (62.3±2.9 vs. 14.4±3.8, p<0.0001) and PASMC (22.6±2.3 vs. 11.2±2.0, p<0.001) in patients with PAH versus controls, with similar findings in arterioles. Gene expression of both ET-1 mRNA ((0.213±0.069 vs. 1.06±0.23, p<0.01) and CCL5 (RANTES) (0.16±0.045 vs. 0.26±0.039, p<0.05) was increased in whole lung homogenates from patients with PAH. NF-[kappa]B is activated in pulmonary macrophages, lymphocytes, endothelial and PASMC in patients with end-stage idiopathic PAH. Future research should determine whether NF-[kappa]B activation is a driver or bystander of pulmonary vascular inflammation and if the former, its potential role as a therapeutic target.